The big book of knowledge : an encyclopedia of questions and answers - Spurgeon, Maureen (Brown Watson London, 2005)
The Big Book of Knowledge: An Encyclopedia of Questions and Answers is an engaging and informative resource that addresses a wide range of questions across diverse subjects. Designed for curious young readers, the book covers topics such as science, history, geography, nature, technology, and the human body. Each section provides clear, concise answers to common questions, enhanced by colorful illustrations and diagrams to make learning fun and accessible. This encyclopedia encourages curiosity and discovery, making it an ideal reference for children eager to explore the world around them and find answers to their many questions.